2017
DOI: 10.1037/tep0000150
|View full text |Cite
|
Sign up to set email alerts
|

Training in trauma psychology: A national survey of doctoral graduate programs.

Abstract: With the high prevalence of potentially traumatic events and subsequent associated mental health problems and impaired functioning, there is a need for graduate training in trauma psychology. A national survey was conducted of all North American doctoral programs in psychology to ascertain the current status of training in trauma. Training directors were sent email invitations and asked to complete a Web based survey. A total of 151 out of 398 responded with adequate information about their program, and were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
(40 reference statements)
0
17
0
1
Order By: Relevance
“…Only four offered a formal trauma course and it was a required course in only one of those programs (1 out of 38, or 2.6% of the schools). In the most comprehensive evaluation of the availability of graduate trauma courses to date, Cook et al (2017) reported findings of their survey of the 398 APA-accredited doctoral programs listed in the Association of Postdoctoral and Internship Centers’ (APPIC) Academic Programs in Psychology directory to determine how many programs were currently providing trauma training through clinical training experiences, academic courses, or both; 38% of the training directors contacted provided data. The results are worrisome: only 20% of these programs reported that they provided both practicum experiences with traumatized populations and at least one course specifically related to traumatic stress.…”
Section: The Current Availability Of Graduate-level Trauma Trainingmentioning
confidence: 99%
“…Only four offered a formal trauma course and it was a required course in only one of those programs (1 out of 38, or 2.6% of the schools). In the most comprehensive evaluation of the availability of graduate trauma courses to date, Cook et al (2017) reported findings of their survey of the 398 APA-accredited doctoral programs listed in the Association of Postdoctoral and Internship Centers’ (APPIC) Academic Programs in Psychology directory to determine how many programs were currently providing trauma training through clinical training experiences, academic courses, or both; 38% of the training directors contacted provided data. The results are worrisome: only 20% of these programs reported that they provided both practicum experiences with traumatized populations and at least one course specifically related to traumatic stress.…”
Section: The Current Availability Of Graduate-level Trauma Trainingmentioning
confidence: 99%
“…Graduate-level training in trauma psychology appears to be inconsistent and sparse. In an investigation over 150 doctoral-level programs across the United States, Cook, Simiola, Ellis, and Thompson (2017) found only one in five offered a trauma psychology course and a practicum specifically working with traumatized populations. Similarly, in a separate study of psychology internship programs, Simiola and colleagues (2018) found that although nearly all sites reported at least one training activity (i.e., supervision or didactic) focused on trauma/PTSD, the breadth and depth of training was low, with less than a third of programs offering training opportunities in trauma/PTSD above the median threshold, which was operationalized based on the frequency and range of training activities offered by the programs (i.e., the number of hours and type of didactic training and/or supervision in trauma/PTSD).…”
Section: What Psychology Students Are Learning and Providers Doingmentioning
confidence: 99%
“…As previously noted, prepracticum typically spans only the first year of training. As such, dedicated courses focused on disorder specific treatment in all of these areas is not likely to be feasible and speaks to the importance of integrative approaches during prepracticum training (e.g., Cook, Simiola, Ellis, & Thompson, 2017). Even within that context though, training in smoking cessation and treatments pertaining to sexual concerns or sleep disorders is clearly lagging and in need of attention (Kleinfelder, Price, Dake, Jordan, & Price, 2012; Meltzer, Phillips, & Mindell, 2009; Miller & Byers, 2008).…”
Section: Practicum Trainee Selectionmentioning
confidence: 99%